UPAYA MENINGKATKAN KEMAMPUAN MENULIS CERITA PENDEK DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA SISWA KELAS V DI SD NEGERI KATONGAN I - SUWARDI SUWARDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The research was conducted from July to November 2022 through cycles. This study used serial image media, with observation and reflection data collection techniques in this classroom action research was carried out using a qualitative descriptive technique. The increase in students' ability to write from cycle to cycle can be seen from the table in cycle 1, the average student learning completeness reached a score of 74.47 on sufficient criteria, with the percentage of students with sufficient criteria as many as 11 children or 65%. 6 students or 35% have completed. Cycle I data on student activity was the total value of 1372 and the average value of 80.70 while in the results of writing the value obtained was 1249 with an average value of 73.47 while the research results in the second cycle of activity data were 1401, with an average of 82.41. Data on students' writing work in cycle II was 1332 with an average of 78.32. From the data from cycle 1 to cycle 2, it can be concluded that writing short stories using serial picture props increases completeness and learning outcomes with a final score on student activity of 1401 with an average score of 82.41 and on student work 1332 with an average score of 78.32 with the criteria of